Identification of Aquifer Vulnerability to Pollution Based on GIS in Jekan Raya and Sabangau Districts Palangka Raya City, Central Kalimantan Province - Prayetno Prayetno; Hendrik Segah; Deddy NSP Tanggara (International Journal Labs, 2023)
Groundwater is the main source of needs for living things. Groundwater is stored in aquifer systems contained in the soil. Under certain conditions, aquifers will be very vulnerable to pollution that can be caused by various sources of pollution depending on existing geological conditions. Therefore, it is necessary to identify the vulnerability of aquifers to polluting sources so that they can assist the government in planning and formulating policies related to regional spatial planning. Identification of aquifer vulnerability can be done using the DRASTIC method which is a weighting method of various parameters such as groundwater table depth (D), Rainfall (R), aquifer media (A), soil media (S), Topography (T), Unsaturated zone (I), and hydraulics conductivity (C) and combined with HAI (Human Activity Impact). The weighting results will produce a Static and Dynamic Aquifer Vulnerability Map. The two maps will be stacked with the Spatial Plans of Palangka Raya City so that it is expected to be a consideration for the Palangka Raya City government in the preparation of the next Regional Spatial Planning policy. The results of weighting with the DRASTIC Index and HAI whole Jekan Raya District and Sabangau District, Palangka Raya City are included in a high level of vulnerability which at this level is an area that is very easy to be polluted by all pollutants, so proper handling is needed so that the impact that will be caused is not too high risk for the condition of aquifers in the area.